Analysis of Elementary School Student's Mathematical Communication Ability on Statistics - Roswahyuliani, Lestari; Putra, Harry Dwi; Widiartini, Amas; Hendriana, Heris ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Students' difficulty in communicating a problem into a mathematical model is one of the important things that must be corrected. This research was carried out based on the results of a preliminary study which showed that students' mathematical communication skills in statistics material were stull low. This study aims to determine students' difficulties in solving application problems. The research method used in this research is qualitative. This research was conducted in an elementary school in West Bandung Regency with 32 V class students as subjects. The instruments used in this study were a descprition test consisting of four questions and interviews. The indicators of mathematical communication used are : (1) Expressing everyday events in symbols or mathematical language, (2) Explain ideas, situations, and mathematical relations with real objects, pictures, graphs, and algebra, (3) Expressing images in the form of ordinary language, (4) Read with comprehension a written mathematical presentation The results of the study show that students still have difficulty communicating the given application problems, especially in making diagrams. Students feel confused in communicating from ordinary forms into diagrammatic forms. Students are confused in determining the value and frequency in the form of a diagram. students also have difficulty reading diagrams and changing the results of the diagrams into ordinary language.